Key Opportunities of E-Learning during COVID-19 Pandemic: A Case Study in One Cambodian High School - Sey, Kassy (MASI Mandiri Edukasi, 2023)
This case study was to investigate the key opportunities of e-learning during the COVID-19 pandemic in one Cambodian high school. A qualitative method was used in this study. There were three high school students participating in the interview process. Purposive sampling was employed. Findings highlighted that students faced many problems during their online classes. However, COVID-19 also provided good opportunities for them such as acquiring new knowledge, get used to online activities that they did not have experienced before, improve self-responsibility and flexibility, and become independent learners; moreover, the result of this study suggested that e-learning also helped the students to save their time, gas and money. They did not have to drive to school; students and teachers stayed home and used the internet wherever it worked. Further study should be conducted in higher education related to e-learning opportunities, and more people should participate in the study.